When Victims Become Suspects: Legal Aspect of Criminalization on Amaq Sinta Case of Spoliation - Erhuma, Ahmed; Maulana, Ahmad; Naron, Phassakorn (Law Research Review Quarterly, 2023)
In recent months, a controversial incident has stirred public discourse, wherein a victim of a "begal" crime found themselves implicated as a suspect and detained by law enforcement. This development raises concerns about the discernment exercised by authorities in rendering decisions without meticulous consideration and logical evaluation. The victim faces charges under Article 338 of the Criminal Code, pertaining to the unlawful taking of a person's life, and Article 351, paragraph 3, concerning assault leading to the loss of life. The employed research methodology adopts a descriptive approach, facilitating a problem-solving investigation by delineating the conditions of the subject or object under study, which may encompass individuals, institutions, or communities based on observable facts. This study adheres to a qualitative research approach, prioritizing an in-depth understanding of the problem over generalization. The secondary research involves data derived from secondary sources, not obtained directly from the primary source. The dual focus addresses two primary inquiries: first, why can a victim facing a charge of taking someone's life be subjected to imprisonment? Second, does victimology maintain relevance within the criminal justice system in Indonesia? The discerned conclusion underscores the imperative for law enforcement officials to exercise heightened prudence when handling cases involving victims turned suspects. It advocates for a judicious approach, combining firmness and logical analysis in decision-making processes and the apprehension of individuals involved in criminal incidents. This scrutiny is pivotal to ensure the equitable and just treatment of all parties within the criminal justice system.